Avaliação da citotoxicidade e genotoxicidade da fosfolipase A2 BnSP-6, isolada da peçonha de Bothrops pauloensis sobre células de câncer de mama MDA-MB-231: uma análise sobre o ciclo celular - Silva, Makswell Almeida (2016)
Herein we evaluated the genotoxic effects of BnSP-6, a Lys-49 phospholipase A2 (PLA2) from Bothrops pauloensis, on breast cancer cells. BnSP-6 was able to induce a higher cytotoxic and genotoxic activity in MDA-MB-231 cells, when compared to MCF10A (a non-tumorigenic breast cell line), suggesting that this protein presented a possible preference for cancer cells. BnSP-6 inhibited MDA-MB-231 proliferation at 24, 48 and 72 hours. In addition, BnSP-6 induced significant increase in the percentage of TUNEL-positive cells, a marker of DNA damage. To obtain novel insight into the direct DNA damage interference in MDA-MB-231 survival and proliferation, we evaluated cell cycle progression. BnSP-6 produced a significant decrease in 2N (G1) and an increase in the G2/M phase and this capacity is likely related to the modulation of expression of progression cell cycle-associated genes (CCND1, CCNE1, CDC25A, CHEK2, E2F1, CDH-1 and NF-kB). Taken together, these results indicate that BnSP-6 induces DNA damage in breast cancer cells and is an attractive model for developing innovative therapeutic agents against breast cancer.